Experimental Evaluation of the Lubrication Performance of Garlic Oil Based MQL in Machining of EN24 Steel - Mohammad Arif Parray; Suhail Shahzad; M. Jebran Khan; Fatima Farooq Bisati; Asif Manzoor; Qurat ul Ain (Tribology Online)
This study explores the remarkable potential of garlic oil as a green, high-performance lubricant in machining, aiming to elevate wear resistance, reduce cutting temperatures, and improve surface finishes, all in contrast to conventional dry cutting methods. Through Scanning Electron Microscopy (SEM), intricate wear patterns on tungsten carbide (WC) tool inserts were meticulously analyzed, while Energy Dispersive X-ray Spectroscopy (EDS) unveiled the adhesive behavior influenced by the garlic oil-based lubrication. Surface roughness, following the turning operation, was elegantly measured using stylus profilometry. The results reveal that garlic oil-based Minimum Quantity Lubrication (MQL) achieved a 43.8% reduction in flank wear, a 69.3% decrease in cutting temperatures, and an impressive 79.3% improvement in surface finish. These findings illuminate garlic oil’s ability to maintain cooler cutting zones, significantly extending tool life while preserving the precision of machined parts. This research underscores the promise of garlic oil as a natural, eco-friendly lubricant, paving the way for sustainable machining practices that not only protect the environment but also ensure unparalleled performance in the processing of EN24 steel.